Core–shell PVA/gelatin nanofibrous scaffolds using co‐solvent, aqueous electrospinning: Toward a green approach. Issue 32 (2nd May 2018) - Sengor, Mustafa; Ozgun, Alp; Corapcioglu, Gulcan; Ipekoglu, Mehmet; Garipcan, Bora; Ersoy, Nuri; Altintas, Sabri
ABSTRACT: Electrospinning (ES) of gelatin often requires cytotoxic organic solvents or acidic environments, which deteriorate cell recognition sites. In this study, aqueous, non‐toxic, co‐solvent ES was performed to obtain core–shell poly(vinyl alcohol) (PVA)/gelatin nanofiber scaffolds. Effects of the core/shell feed rate ratio (FRR) were investigated on a morphological and mechanical basis. PVA:gelatin ratio of 1:4 was the limiting ratio for specific voltage and electrode distance parameters to obtain uniform fibers. Core–shell bead‐free structures were obtained at 8% PVA and gelatin aqueous solutions. A mean diameter of 280 nm was obtained for 1:1 FRR at 15 kV and 15 cm of electrode distance. Crosslinking resulted in slight improvement in tensile strengths and severe decrease in ductility. Fourier transform infrared spectra revealed retention and improvement of stable secondary structures of gelatin after ES. The scaffolds almost degraded more than 60% in 14 days. Based on the results, present scaffolds hold great promise as suitable candidates for biomedical applications. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46582. Abstract :